2021
DOI: 10.1080/02656736.2021.1973585
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided high intensity focused ultrasound ablation for uterine fibroids: long-term outcomes and factors affecting local recurrence

Abstract: Objective: To assess the long-term outcomes and the factors affecting local recurrence of uterine fibroids after ultrasound-guided high-intensity focused ultrasound (USgHIFU) ablation. Materials and methods: 629 patients with a solitary uterine fibroid smaller than 10 cm in diameter treated with USgHIFU at our institutes between January 2011 and December 2016 were retrospectively analyzed. The patients were requested to take pre-HIFU and one day post-HIFU MRI. The patients were asked to return to the hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…This strategy was also applied to volume measurements during follow‐up. An increase in RMV at the follow‐up MRI exam of greater than 10% from that in the immediate postoperative period (1 day post HIFU) was set as the criterion for identifying residual myoma regrowth 1 , and open‐source software (ITK‐SNAP v3.8.0, http://www.itksnap.org) was used to segment regions of interest (ROIs) on T2WI obtained within 1 day post HIFU, layer‐by‐layer along the edges of the myoma. The feature identification and image segmentation outlined above were validated by another radiologist (Reader 2) with 16 years' experience in pelvic radiography; in the case of disagreement, Reader 2 retraced the ROI and this was used as the final decision.…”
Section: Methodsmentioning
confidence: 99%
“…This strategy was also applied to volume measurements during follow‐up. An increase in RMV at the follow‐up MRI exam of greater than 10% from that in the immediate postoperative period (1 day post HIFU) was set as the criterion for identifying residual myoma regrowth 1 , and open‐source software (ITK‐SNAP v3.8.0, http://www.itksnap.org) was used to segment regions of interest (ROIs) on T2WI obtained within 1 day post HIFU, layer‐by‐layer along the edges of the myoma. The feature identification and image segmentation outlined above were validated by another radiologist (Reader 2) with 16 years' experience in pelvic radiography; in the case of disagreement, Reader 2 retraced the ROI and this was used as the final decision.…”
Section: Methodsmentioning
confidence: 99%
“…The application of training evaluation indicators was based on benefits for patients and growth rules for novice physicians. NPV ratio was negatively correlated with reintervention rate, 10–12 so 80% NPV ratio was better than 70% NPV ratio. But the LC‐CUSUM results showed that the corresponding learning period was also longer, and it took more time and cost.…”
Section: Discussionmentioning
confidence: 86%
“…The mean NPV ratio reached 87.2% whilst adverse effects remained infrequent 9 . The NPV ratio (the ratio of the nonperfused area volume to the fibroid volume) has been proved to be negatively correlated with re‐intervention rate, which means that with the increase of NPV ratio, the re‐intervention rate of patients exhibits a trend of decrease 10–12 . Previous study has indicated that when NPV ratio reached 80%, the re‐intervention rate of patients was about 5% 12 months after HIFU ablation 9 …”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, we did not find a relevant correlation between the relative SI of the fibroids and relative volume reduction. However, the discrepancy in the relative volume reduction could not be explained by different treatment characteristics, as the NPV—which was shown to be a relevant factor for the outcome of HIFU therapy [ 22 ]—was similar in both groups. In our study, the mean baseline volume of SF was slightly higher than that of the treated fibroids for patients with MF.…”
Section: Discussionmentioning
confidence: 99%